Calix[4]arene-based rotaxane host systems for anion recognition. - McConnell, A; Serpell, C; Thompson, A; Allan, DR; Beer, P (2010)
The synthesis, structure and anion binding properties of the first calix[4]arene-based [2]rotaxane anion host systems are described. Rotaxanes 9.Cl and 12.Cl, consisting of a calix[4]arene functionalised macrocycle wheel and different pyridinium axle components, are prepared via adaption of an anion templated synthetic strategy to investigate the effect of preorganisation of the interlocked host's binding cavity on anion binding. Rotaxane 12.Cl contains a conformationally flexible pyridinium axle, whereas rotaxane 9.Cl incorporates a more preorganised pyridinium axle component. The X-ray crystal structure of 9.Cl and solution phase (1)H NMR spectroscopy demonstrate the successful interlocking of the calix[4]arene macrocycle and pyridinium axle components in the rotaxane structures. Following removal of the chloride anion template, anion binding studies on the resulting rotaxanes 9.PF(6) and 12.PF(6) reveal the importance of preorganisation of the host binding cavity on anion binding. The more preorganised rotaxane 9.PF(6) is the superior anion host system. The interlocked host cavity is selective for chloride in 1:1 CDCl(3)/CD(3)OD and remains selective for chloride and bromide in 10 % aqueous media over the more basic oxoanions. Rotaxane 12.PF(6) with a relatively conformationally flexible binding cavity is a less effective and discriminating anion host system although the rotaxane still binds halide anions in preference to oxoanions.